2004
DOI: 10.1186/1465-9921-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of NO synthase isoforms after ozone: the effects of allergen exposure

Abstract: Background: The functional role of nitric oxide (NO) and various nitric oxide synthase (NOS) isoforms in asthma remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Jang and colleagues have previously demonstrated nNOS expression in the lung after ozone exposure, but not after allergen exposure, and it is interesting that this was accompanied by a reduction in iNOS expression, consistent with our findings in patients with COPD (29). Higher levels of oxidative and nitrative stress are seen in patients with COPD (21) and we now report an increase in nNOS expression.…”
Section: Choosesupporting
confidence: 92%
See 1 more Smart Citation
“…Jang and colleagues have previously demonstrated nNOS expression in the lung after ozone exposure, but not after allergen exposure, and it is interesting that this was accompanied by a reduction in iNOS expression, consistent with our findings in patients with COPD (29). Higher levels of oxidative and nitrative stress are seen in patients with COPD (21) and we now report an increase in nNOS expression.…”
Section: Choosesupporting
confidence: 92%
“…Jang and colleagues demonstrated that eNOS and nNOS isoforms induce airway responsiveness in mice after ozone exposure, whereas iNOS is decreased, suggesting that eNOS and nNOS contribute to the formation of NO metabolites in mice after ozone exposure (29,41). Grasemann and colleagues investigated the existence of a genetic association between a polymorphism in the nNOS gene and the diagnosis of asthma, concluding that nNOS may be a candidate gene for asthma (42).…”
Section: Choosementioning
confidence: 99%
“…In this study, Arginase I expression was found in airway smooth muscles in smokers but not in non-smokers. Among ambient air pollutants, exposure to high levels of ozone has been also been shown to produce oxidative stress and inflammation which can modulate NOS isoform expressions 16. Therefore, it is plausible that the mechanism for the variation of the association of ARG1 and ARG2 variants with asthma in children with different ambient air pollutant exposures (e.g., ozone, PM 2.5 , etc) could be in part due to differences in arginase isoform expression.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that concentrations of NO metabolites increased with asthma severity in the tracheo-bronchial secretions of asthmatic subjects, and that NO metabolites in sputum are a more valuable indicator for monitoring asthmatic airway inflammation than those in serum . The nitric oxide synthase (NOS) isoforms play different roles in airway inflammation after ozone exposure (Jang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%